Efeito da dieta com e sem volumoso para ovinos em terminação - MENDES, Jéssica Antonia Cardoso (2017)
The objective of this study was to evaluate the effect of the use of a non-voluminous diet on feeding confined sheep on nutrient intake, water intake, performance, nutrient digestibility, ingestive behavior and feed cost analysis. Sixteen male, castrated, mixed Dorper x Santa Inês mongrels were distributed in two treatments with eight replicates and eight complete randomized blocks, according to the initial weight (23,68 ± 4,21 kg). The sheep were placed in individual pens for a period of 65 days, 18 days for the adaptation of the animals to the experimental diets and 44 days for data collection. After the period of confinement, the animals remained for another 3 days in the bays, for the digestibility assay, through total collection of feces. The treatments consisted of a diet with voluminous (with voluminous ratio: concentrate, 30:70) and no voluminous diet (pelleted ration). The dry weight diet, organic matter, crude protein, ethereal extract, neutral detergent fiber, acid detergent fiber, total carbohydrates, non-fibrous carbohydrate, metabolizable energy were reduced (P<0,05); And provided lower average daily weight gain (120,64 g), as well as increased feed conversion (6,82) and water intake per kg of dry matter (3,70 kg/kg MS day) of sheep finished in Confinement. This diet increased (P<0,05) the digestibility of neutral detergent fiber (NDF) and acid detergent fiber (FAD) by 6,7% in relation to the diet with roughage. The lambs fed the non-bulking diet presented the lowest averages (P<0,05) spent with the activities: feeding time (0,84 h/day), feeding frequency (5,50), rumination time (1,22 h/day) and total chewing time (2,53 h/day). The feed time (21,46 h/day), MS ingestion efficiency (1159,02 g MS/ h) and NDF (371,81 g MS/ h), DM rumination efficiency (497,76 g MS/ h) and NDF (158,36 g MS/ h) of the animals fed the no-bulking diet was higher (P<0,05) than the bulky diet. The non-voluminous diet provided a negative profit margin (-13,17 R$/ animal). Therefore, lambs fed the non-bulking diet had lower bieconomic performance.